Analysis of Non Hierarchical Bomb for Collection of Community Health Degrees in Jambi and Muaro Jambi City - Yelli Ramalisa; Azzikra Febriyanti; Cut Multahadah (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2019)
This research purpose to investigate the community health degree in Jambi and Muaro Jambi City using a non-hierarchical cluster. This method based on community health building indicators with 22 sub-districts, eleven in Jambi City and 11 in Muaro Jambi district. The results was basically 22 sub-districts in Jambi City and District. Muaro Jambi already has a fairly good IPKM value, such as South Jambi sub-district, Red Paal, Jambi Market and Teluk Danau based on analysis of hierarchical bomb.